Stabilization by Silicon Compounds of the Allelopathic Soil Regime under Perennial Fruit Plantations - Zaimenko, Nataliia; Pavliuchenko, Nataliia; Klymenko, Svitlana; Dobroskok, Vitaliy; Krupa, Sergiy (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
To optimize the allelopathic soil regime under perennial fruit plantations of M.M. Gryshko National Botanical Garden of NAS of Ukraine the effect of silicon compounds on phytotoxic and biochemical properties of rhizosphere was examined. The organo-mineral mixture with nanoparticles of the natural siliceous mineral analcite was added (the norm of 500 kg/ha) in dark gray podzolized soil under 30-year-old fruit plantations from orchard areas. Soil samples were taken at a depth of 0–20, 20–40, 40–60 cm. Control for each fruit plant was soil without the silicon compounds. The biochemical state of the soil was evaluated by the redox potential (Eh) values. As a result of the addition of siliceous mixture to the soil its Eh increased in total 1.1–1.4 times, indicating a slowdown in the rate of accumulation of labile organic compounds involved in the phenomena of allelopathic interaction and post-action under the fruit plants. The lowest values of soil Eh were in the most enriched with organic matter upper horizon (0–20 cm) both in control and in the presence of silicon compounds. Phenolic allelochemicals concentration decreased in 1.1–3.1 times compared with the control in the soil with the addition of the mixture. The phenolic compounds content was the highest in the upper horizons and gradually decreased in the direction to the lower, which coincided with the revealed general course of redox processes for the investigated soil profiles. At the siliceous mixture influence, the ammoniaс nitrogen amount increased, especially in the soil under the cornel, which may inhibit the synthesis of phenols and prevent phytotoxicity on condition of calcium accumulation. The allelopathic properties of the soil changed due to the improvement its biochemical characteristics by the siliceous mixture action. The growth-stimulatory effect in relation to acceptor plants at 8–55% in comparison with the control was observed. The obtained data showed the efficacy of the silicon compounds use for the reduction of soil sickness in orchards, which is resulted from a decrease in phenolic allelochemicals concentration and phytotoxicity, optimization of redox and nutrient regimes.